Insulin-insensitivity of male genitalia maintains reproductive success in Drosophila. (15th May 2019) - Dreyer, Austin P.; Shingleton, Alexander W.
Abstract : For most arthropod species, male genital size is relatively implastic in response to variation in developmental nutrition, such that the genitals in large well-fed males are similar in size to those in small poorly-fed males. In Drosophila melanogaster, reduced nutritional plasticity of the male genitalia is a consequence of low insulin sensitivity through a tissue-specific reduction in the expression of FOXO, a negative growth regulator . Despite an understanding of the proximate developmental mechanisms regulating organ size, the ultimate evolutionary mechanisms that may have led to reduced FOXO expression in the genitalia have not been fully elucidated. Here we show that restoring FOXO activity in the developing genitalia reduces the male genital size and decreases various aspects of male reproductive success. These data support the hypothesis that sexual selection has acted on the male genitalia to limit their nutritional plasticity through a reduction in FOXO expression, linking proximate with ultimate mechanisms of genital evolution.